A Survey of Suctioning Practices among Physical Therapists, Respiratory Therapists and Nurses - Dina Brooks; Sherra Solway; Ian Graham; Laurie Downes; Margaret Carter (Canadian Respiratory Journal)
OBJECTIVE: To assess the current tracheal and oropharyngeal suctioning practice variability within and among the professions of physical therapy, respiratory therapy and nursing.